Experimental Investigations of Surface Roughness Effect on Functional Applications of Tube Extrusion Punch Using Magnetorheological Finishing Process - Chana, Anirudh (My University, 2018)
Surface finish has great influence on functional properties such as wear resistance and power loss. Finishing process not only has to reduce surface roughness but also improve the surface accuracy and minimize the surface defects. In metal forming process, surface roughness plays the vital role in deciding the efficiency of the process. Rough surface results in more power loss and abrasion of dies and punches during metal forming operations. Non homogenous strain of material due to high surface roughness in forming process results in heterogeneity of properties of end products. Demand for surface finishing of dies and moulds in metal forming processes is increased. The industrial application for surface finishing requirement has various benefits. Surface finish is required to improve the service life of the extrusion punch used in tube extrusion process. In industry, the finishing of the extrusion punch is performed mainly by grinding process. Surface roughness of 480nm is achieved at the industry by the grinding process. A fixture of magnetorheological (MR) finishing process is developed in this research to finish the ferromagnetic cylindrical extrusion punch made of H13 material up to nano-level. The present MR finishing tool performance has been analyzed for finishing of extrusion punch through magnetostatic simulation. The study on the mechanism of material removal during MR finishing of extrusion punch is also done. The surface roughness model is validated experimentally. The percentage error is found in the range of 5% to 15.65%. Response surface methodology (RSM) using central composite design has been used for designing the experiments and regression analysis. The effect of process parameters like tool rotation, tool reciprocating feed, workpiece rotation and current are studied and optimized. Experiments are performed using the optimum parameters. Surface roughness are reduced from 380nm to 50nm in 50 minutes. Finishing of the extrusion punch has been done using optimum parameters on the designed fixture. Surface roughness value of punch reduced to 70nm from 480nm in 25hrs. After finishing, extrusion punch is tested in industry for improvement in tube extrusion process and found their better functional life as compared to the grinded surface.
Keywords: Extrusion punch; Magnetorheological polishing fluid; H13 die steel; Magnetic iron particles; Surface roughness